Feeling dissimilar and helping others? A conceptual analysis. Issue 2 (27th May 2014) - Yung Chou, Shih; Chang, Tree; Han, Bo
Abstract : Purpose: – The purpose of this paper is to explore how perceived visible, work value, and informational dissimilarity affect an individual's helping behavior. Additionally, it investigates the moderating roles of the need for affiliation and need for achievement. Design/methodology/approach: – A theoretical analysis was performed. Findings: – It is proposed that perceived visible, work value, and informational dissimilarity will have a negative impact on an individual's helping behavior. Additionally, it is posited that the need for affiliation and need for achievement will positively moderate the negative relationship between perceived dissimilarity and helping behavior. Research limitations/implications: – This paper provides additional insight into antecedents of helping behavior, and offers a theoretical basis for future research that examines the relationship between subjective diversity and discretionary behaviors in organizations. Practical implications: – This paper has several important implications. First, managers are recommended to implement effective educational approaches, such as role-playing, that help eliminate employees' negative perceptions of dissimilarity and promote willingness to help co-workers. Second, managers should reinforce shared vision, values, and goals, which in turn may encourage interpersonal cooperative behaviors. Third, managers should facilitate the dissemination of knowledge and information that are crucial to individual performance. Fourth, managers are encouraged to provide employees with trainings on effective interpersonal processes such as inclusion and emotional management. Finally, managers should increase the degree of task interdependence, which may promote high levels of helping behavior. Originality/value: – This paper is one of the very few studies that link helping behavior with subjective perceptions of dissimilarity. More importantly, this paper highlights the importance of the interaction between dissimilarity perceptions and internal driving forces.